2002
DOI: 10.1117/12.453227
|View full text |Cite
|
Sign up to set email alerts
|

<title>Fiber coupling with adaptive optics for free-space optical communication</title>

Abstract: We describe an adaptive optical fiber coupling system for free-space optical communication comprising a microelectromechanical deformable mirror and a VLSI gradient descent controller for model-free performance optimization. A comparison of Strehl ratio maximization with direct model-free coupling efficiency optimization revealed an advantage of the latter method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 9 publications
(5 reference statements)
0
21
0
Order By: Relevance
“…When both β and D are fixed, in the case of ζ 1, Eq. (19) is also assumed to be equivalent to the previous equation of η C in Refs. [12] and [13] because of the same spatial coherent radius obtained, which is not presented here.…”
Section: Analysis Of Spatial Coherent Radiusmentioning
confidence: 99%
See 1 more Smart Citation
“…When both β and D are fixed, in the case of ζ 1, Eq. (19) is also assumed to be equivalent to the previous equation of η C in Refs. [12] and [13] because of the same spatial coherent radius obtained, which is not presented here.…”
Section: Analysis Of Spatial Coherent Radiusmentioning
confidence: 99%
“…A host of research has focused on the fiber-coupling efficiency of the SMF [12][13][14][15][16][17][18][19][20][21]. The fiber-coupling efficiency of an ideally coherent laser source through atmospheric turbulence has been discussed previously, and the results have been applied to lidar and free-space optical communication [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In 1997, Vorontsov and colleagues at the U.S. Army Research Laboratory used this algorithm in adaptive optical imaging and achieved major success [22][23][24], after which it was formally named the stochastic parallel gradient descent (SPGD) algorithm. Its relatively traditional optimization method has the obvious advantage of rapid convergence, and it is currently used in research and applications in many different fields such as free-space visible light communication [25], VLSI microchips [26,27], fiber optic array phase lockers [28], synthesis pore adaptive imaging [29], and laser communications [30].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated a 12 dB improvement in the coupling efficiency in laboratory with this system. A similar system was also used to compare blind optimization with a conventional AO system based on wavefront conjugation, and it was found that using the coupling efficiency as a feedback signal in the AO system could provide better results [2].…”
mentioning
confidence: 99%